Intensity of physical activity among school going adolescents in Chennai, South India - S. M., Balaji; R. C., Karthik; R., Durga; S., Harinie; M., Ezhilvanan (International Journal Of Community Medicine And Public Health, 2018)
Background: Insufficient physical activity is one of the leading risk factors for global mortality and is on the rise in many countries, adding to the burden of NCDs and affecting general health worldwide. People who are insufficiently active have a 20% to 30% increased risk of death compared to people who are sufficiently active. Objective of the study was to assess the intensity of physical activity among school going adolescents aged 13–17 years. Methods: A cross sectional study was done among school going adolescents aged 13 – 17 years in 2 semi urban schools. About 235 subjects were selected and administered with a modified GPAQ questionnaire which measured the physical activity of the students in METs (metabolic equivalent). Results: The median intensity of physical activity among the study population was 500 METs (IQR 360 – 800). Among the study population, 148 (63%) adolescents were insufficiently physically active (< 600 METs) out of which females were 84 (57%). Among the adolescents, insufficient physical activity was significantly higher among females and among 16-17 years than 13-15 years age group.Academic stress and no space near their home for playing were found to be associated with insufficient physical activity. Conclusions:The prevalence of insufficient physical activity is very high among adolescents especially more among females. Reducing the academic burden and inclusion of physical activity classes in regular academic schedule and proper motivation from parents are required to improve physical activity among adolescents.